Community preferences in general practice: important factors for choosing a general practitioner. (7th January 2015) - Kenny, Patricia; De Abreu Lourenco, Richard; Wong, Chun Yee; Haas, Marion; Goodall, Stephen
Abstract: Background: Understanding the important factors for choosing a general practitioner (GP) can inform the provision of consumer information and contribute to the design of primary care services. Objective: To identify the factors considered important when choosing a GP and to explore subgroup differences. Design: An online survey asked about the respondent's experience of GP care and included 36 questions on characteristics important to the choice of GP. Participants: An Australian population sample ( n = 2481) of adults aged 16 or more. Methods: Principal components analysis identified dimensions for the creation of summated scales, and regression analysis was used to identify patient characteristics associated with each scale. Results: The 36 questions were combined into five scales (score range 1–5) labelled: care quality, types of services, availability, cost and practice characteristics. Care quality was the most important factor (mean = 4.4, SD = 0.6) which included questions about technical care, interpersonal care and continuity. Cost (including financial and time cost) was also important (mean = 4.1, SD = 0.6). The least important factor was types of services (mean = 3.3, SD = 0.9), which covered the range of different services provided by or co‐located with the practice. Frequent GP users and females had higher scores across all 5 scales, while the importance of care quality increased with age. Conclusions: When choosing a GP, information about the quality of care would be most useful to consumers. Respondents varied in the importance given to some factors including types of services, suggesting the need for a range of alternative primary care services.